(untitled) (Eastern Medical College Journal, 2023)
Background: Asthma is a well-known chronic respiratory disease and a common global health problem. In Bangladesh, more than 100 million people are suffering from cough and shortness of breath. Patients with a known diagnosis of asthma are an important determinant of reduced quality of life. Objectives: To determine the quality of life and its accompanying factors among adult female patients with chronic bronchial asthma. Materials and methods: This cross-sectional study was conducted at the National Institute of Diseases of the Chest and Hospital, Dhaka from January to December 2021. Total eighty-five diagnosed adult female bronchial asthma patients were included in this study. Data were collected by face-to-face interviews with a semi-structured questionnaire using the Asthma Quality of Life Questionnaire (AQLQ) and Asthma Control Test (ACT) scale. The checklist was used for collecting data by reviewing medical records. Results: Among all the patients, the mean (±SD) age was 39.74±8.98 years and the highest frequency 48 (56.5%) patient’s age were in the 31-45 years group. In this study, the mean AQLQ score was 3.55 so, it indicated a moderate degree of impairment of quality of life and the most affected domain was environmental stimuli. Among all patients, 52 (61.2%) had partially controlled asthma. The study finding showed that the level of impairment of quality of life decreased with the increase of age (p=0.001). Uncontrolled asthma was associated with a lower quality of life (p=0.001). The low educational level 25 (29.4%), residing in rural areas 26 (30.6%) and having comorbidity 44 (51.8%) adversely affected the level of AQLQ. Conclusion: Now a day’s chronic bronchial asthma is a major public health issue, and it affects the quality of life. So, the current study may contribute to the prevention of worsening the level of impairment of quality of life in bronchial asthma patients. Eastern Med Coll J. July 2023; 8 (2):61-67